Understanding Predictors of Lifelong Initiation and Follow-up Treatment for adolescents and youth living with HIV (UPLIFT): an integrated prospective cohort in Eastern Cape, South Africa - Gayle Sherman; Nontokozo Langwenya; Elona Toska; Lucie Dale Cluver; Janke Tolmay; Janina Jochim; Siyanai Zhou; Olanrewaju Edun; Zea Leon (BMJ Open, 2025)
Purpose Adolescents living with HIV (ALHIV) are a priority population for achieving global HIV prevention and treatment targets but experience poorer outcomes than adults. Long-term follow-up is essential to understand their transition into adulthood. By linking self-reported survey data with routine laboratory records, we established a social science clinical cohort of ALHIV South Africa’s Eastern Cape to explore factors shaping their long-term health and well-being.Participants Eligible participants were adolescents who were part of a three-wave quantitative cohort of ALHIV and not living with HIV (2014–2018) and had consented (adolescent and caregiver) to having their self-reported interviews linked with routine health records (n=1563). Adolescents were recruited into the existing three-wave cohort through clinic and community-based methods (97% enrolment, >90% retention over three waves). Between 2019 and 2022, we abstracted laboratory test records from the National Health Laboratory Services database for all eligible participants, with matching based on demographic variables. Individuals with at least one HIV-related record form our ‘lifelong social science cohort’, a total of 956 ALHIV (852 of 1107 ALHIV and 104 of 456 HIV-uninfected).Findings to date A total of 32 886 laboratory test records from 2004 to 2023 were matched through three rounds of data extraction, using iteratively refined record-linking searches. Most records were viral load (8864) and CD4 count (6801) results, with a median of 10 (IQR: 7–14) and 8 (IQR: 5–11) tests per matched adolescent, respectively. Overall, 956 of 1563 adolescents (61%) were successfully linked to laboratory data, including 852 of 1107 (77%) ALHIV. Analysis of the matched cohort survey-laboratory data provided several insights. Self-reported antiretroviral therapy adherence was strongly associated with viral suppression, even after adjusting for covariates. The strongest predictors of suppression were not reporting missed doses in the past 3 days, past week and not missing clinic appointments in the past year. Among adolescent girls and young women living with HIV, access to safe and affordable facilities, and kind and respectful staff were associated with a higher likelihood of multiple improved HIV-related outcomes, including viral suppression. Exposure to sexual and intimate partner violence predicted worse viral load outcomes among adolescents.Future plans This integrated prospective cohort provides an opportunity to characterise long-term HIV treatment outcomes among ALHIV in Africa. We will investigate how individual, familial, community and healthcare experiences in childhood, and adolescence shape these outcomes. Since the COVID-19 pandemic happened during the period of matched data, we will also investigate the potential effect of the COVID-19 pandemic on adolescent HIV treatment outcomes, with potential subgroup analyses for individuals with available COVID-19-related results.